Pengaruh Inovasi Layanan Sinergi Imigrasi Antar Pulau (SILAU) Terhadap Kepuasan Pegawai Melalui Kondisi Kerja - Palentin Enjelika Turnip; Imam Yudhi Prastya; Reza Gemilang (CV. ITTC INDONESIA, 2026)
This study aims to analyze the effect of the Sinergi Imigrasi Antar Pulau (SILAU) service innovation on employee satisfaction through working conditions at the Class II TPI Immigration Office of Tanjung Balai Karimun. This study employed a quantitative approach with 37 employees as the sample using a saturated sampling technique. Data were collected through questionnaires and analyzed using IBM SPSS Statistics 25 with Hayes PROCESS Macro Model 4 and 5,000 bootstrap samples. The results showed that SILAU service innovation had a positive and significant effect on working conditions. Working conditions also had a positive and significant effect on employee satisfaction. However, SILAU service innovation did not have a significant direct effect on employee satisfaction. The mediation test showed that working conditions mediated the effect of SILAU service innovation on employee satisfaction, with an indirect effect of 0.971 and a confidence interval ranging from 0.612 to 1.371. These findings indicate that increased employee satisfaction through SILAU occurs when the innovation is accompanied by supportive working conditions.